Abortion rights : for and against - Greasley, Kate; Kaczor, Christopher Robert, 1969- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2018)
"This book features opening arguments followed by two rounds of reply between two moral philosophers on opposing sides of the abortion debate. In the opening essays, Kate Greasley and Christopher Kaczor lay out what they take to be the best case for and against abortion rights. In the ensuing dialogue, they engage with each other's arguments and each responds to criticisms fielded by the other. Their conversational argument explores such fundamental questions as: what gives a person the right to life? Is abortion bad for women? What is the difference between abortion and infanticide? Underpinned by philosophical reasoning and methodology, this book provides opposing and clearly structured perspectives on a highly emotive and controversial issue. The result gives readers a window into how moral philosophers argue about the contentious issue of abortion rights, and an in-depth analysis of the compelling arguments on both sides."--
In defense of abortion rights / Kate Greasley -- Abortion as human rights violation / Christopher Kaczor -- A reply to Kaczor / Kate Greasley -- A reply to "In defense of abortion rights" / Christopher Kaczor -- A short reply to the reply / Kate Greasley -- A short reply to Greasley / Christopher Kaczor.
Includes bibliographical references and index.
Keywords: Abortion -- Law and legislation; Fetus -- Legal status, laws, etc; Human rights; Abortion -- Law and legislation; Fetus -- Legal status, laws, etc; Human rights; Ethik; Schwangerschaftsabbruch